2020
DOI: 10.1111/obr.13148
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful weight loss outcomes amongst individuals with obesity undergoing lifestyle interventions: A systematic review

Abstract: Summary Understanding the predictors of weight loss with lifestyle interventions can help to ascertain the probable outcomes of individuals with obesity who undergo such interventions. This systematic review assessed the evidence of predictors of successful weight loss among individuals who are overweight or with obesity undergoing lifestyle interventions. Four electronic databases (PubMed, Cochrane Reviews, PsychInfo and Wiley) were searched to find relevant literature published in the past 20 years. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 43 publications
6
58
2
1
Order By: Relevance
“…Some multidimensional approaches have been proposed for the prevention and management of overweight and obesity. Most are based on increasing physical activity and improving diet quality [ 3 , 4 , 5 ] to counteract energy imbalance and, thereby, avoid weight gain [ 6 ]. In this context, in line with dietary guidelines aimed at reducing total energy intake and improving diet quality, recent studies have reinforced the importance of replacing the intake of unhealthy foods between main meals for nutrient-dense foods, such as nuts [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some multidimensional approaches have been proposed for the prevention and management of overweight and obesity. Most are based on increasing physical activity and improving diet quality [ 3 , 4 , 5 ] to counteract energy imbalance and, thereby, avoid weight gain [ 6 ]. In this context, in line with dietary guidelines aimed at reducing total energy intake and improving diet quality, recent studies have reinforced the importance of replacing the intake of unhealthy foods between main meals for nutrient-dense foods, such as nuts [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous studies showing that adherence to healthy dietary patterns, rather than restrictive diets, plays a key role in the effectiveness of weight loss among patients undergoing EBTs [ 15 , 16 ]. The latter implies that patients with obesity undergoing EBTs should not simply be on a “diet”; instead, weight loss therapy should include a series of behavioral changes that facilitate healthier eating and becoming more active [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is relevant to understand what makes patients undergoing EBTs achieve a weight loss comparable to bariatric surgery. Besides the adherence to healthy lifestyle habits, lessons from lifestyle intervention programs for people with obesity have taught that weight loss success could be linked to eating behaviors (such as emotional eating) and psychological traits (anxiety and depression) [ 18 , 19 , 20 , 21 ], all of which are associated with weight loss success, but also with the abandonment (or drop out) of weight loss programs [ 19 , 20 , 21 ]. Furthermore, a pivotal study by Pontiroli et al [ 22 ] showed that compliance to the rules recommended after bariatric surgery was significantly associated with personality traits such as narcissism.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the weight loss journey is affected by variation in the levels of motivation, facilitators, and barriers that are specific to each participant. [3][4][5] An in-depth exploration of the perception of menopausal women related to weight status, motivation for weight loss, preferred measures of weight loss, perceived barriers, and facilitators experienced during the weight loss journey may help in improving the effectiveness of current lifestyle modification strategies. A few qualitative studies have attempted to understand the weight loss related perceived motivators, barriers, and facilitators in menopausal women residing in the west.…”
mentioning
confidence: 99%